2016
DOI: 10.1177/0896920515580176
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing Work: The Influence of Workplace History and Perceptions of the Future on Lean Production at Three GM Plants

Abstract: Research recognizes both a tension between standardized work and employee participation as well as the fact that management and labor negotiate both formally and informally over the reorganization of work. Through a comparison of the lean production systems being implemented at three General Motors assembly plants, this article demonstrates the tension between standardization and participation to be socially constructed due, in part, to workplace historical context. Workplace history shapes the attitudes of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These principles include team work, communication, continuous improvement and the efficient use of human resources (Womack et al ., 1990). The concept of multifunctional teams is core to lean practices and work groups are expected to be fully responsible for their work area and portion of the production process (Ahlstrom, 1998; Rothstein, 2015). Indeed, Womack et al .…”
Section: Introduction and Outlinementioning
confidence: 99%
“…These principles include team work, communication, continuous improvement and the efficient use of human resources (Womack et al ., 1990). The concept of multifunctional teams is core to lean practices and work groups are expected to be fully responsible for their work area and portion of the production process (Ahlstrom, 1998; Rothstein, 2015). Indeed, Womack et al .…”
Section: Introduction and Outlinementioning
confidence: 99%
“…Research has shown that new management systems and work practices are often selected and implemented in a way that is shaped by the social and organisational forces surrounding their implementation (Vidal, 2007b). The tension between work standardisation and participation could be viewed as socially constructed, based on the historical context of the workplace (Rothstein, 2016). In China, those established organisational routines that SOEs have maintained may be opposed to the rapid changes in formal rules, giving rise to both opposition norms and structural inertia (Nee, 2005).…”
Section: Employees' Acceptance Of New Management Systemsmentioning
confidence: 99%
“…Elger and Smith (2005), for instance, reconstruct the complex "micropolitical processes" involved in adapting lean production at various Japanese transplants in Great Britain. In a more recent analysis, Rothstein (2016) explains the differences between the production systems at the Mexican and United States (US) plants of an American automotive company as being related to various strategies of local unions and, most importantly, to different levels of industrial experience among the local workforces.…”
Section: Local Labour Control Regimes and Worker Agencymentioning
confidence: 99%